2001
DOI: 10.1006/qres.2001.2264
|View full text |Cite
|
Sign up to set email alerts
|

Tropical Rain Forest and Climate Dynamics of the Atlantic Lowland, Southern Brazil, during the Late Quaternary

Abstract: Palynological analysis of a core from the Atlantic rain forest region in Brazil provides unprecedented insight into late Quaternary vegetational and climate dynamics within this southern tropical lowland. The 576-cm-long sediment core is from a former beachridge "valley," located 3 km inland from the Atlantic Ocean. Radiocarbon dates suggest that sediment deposition began prior to 35,000 14 C yr B.P. Between ca. 37,500 and ca. 27,500 14 C yr B.P. and during the last glacial maximum (LGM; ca. 27,500 to ca. 14,5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
112
0
22

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(150 citation statements)
references
References 10 publications
8
112
0
22
Order By: Relevance
“…Thus, the estimated divergence between the populations of C. bimaculatus from the northern and southern Mata Atlântica (2.2-4 MYA; Fig. 2) is in agreement with phylogeographic evidence from pitviper populations in this region, showing a divergence of 3.8 MYA in the wake of orogenic events that caused changes in precipitation regimes and fragmentation of the Atlantic Forest (21,22). The genetic split between these lineages is supported by the fixation of subtle morphological differences.…”
Section: Discussionsupporting
confidence: 82%
“…Thus, the estimated divergence between the populations of C. bimaculatus from the northern and southern Mata Atlântica (2.2-4 MYA; Fig. 2) is in agreement with phylogeographic evidence from pitviper populations in this region, showing a divergence of 3.8 MYA in the wake of orogenic events that caused changes in precipitation regimes and fragmentation of the Atlantic Forest (21,22). The genetic split between these lineages is supported by the fixation of subtle morphological differences.…”
Section: Discussionsupporting
confidence: 82%
“…Coral-based (Guilderson et al 1994) and foraminifera-based (Mix et al 1999) tropical sea-surface temperature reconstructions and analyses of noble gas concentrations in Brazilian groundwater (Stute et al 1995) show a maximum LGM tropical cooling of 5°C. Brazilian palynological data suggest a cooling of between 3 and 7°C (Behling & Negrelle 2001;Behling 2002). Kaolinite oxygen and hydrogen isotopes in palaeosols from the Colombian Bogotá basin suggest an LGM cooling of 5-7°C (Mora & Pratt 2001 temperatures up to 12°C lower during the LGM (Thompson et al 1995(Thompson et al , 1998, although this interpretation has since been reassessed to be more in the region of 3°C (for more details see Pierrehumbert 1999).…”
Section: (B) Climate Scenarios and Simulationsmentioning
confidence: 99%
“…Few studies based on palynology have demonstrated the permanence of the Atlantic Forest during the entire Holocene (e.g. Behling and Negrelle 2001). Most of these studies propose forest expansion or modification of forest species composition during the late Holocene, in response to inferred more humid climates.…”
Section: Introductionmentioning
confidence: 99%